Intimate partner violence among reproductive-age women with chronic mental illness attending a psychiatry outpatient department: cross-sectional facility-based study, Addis Ababa, Ethiopia - Delayehu Bekele; Markos Tesfaye; Tigist Zerihun (BMJ Open)
Objective To determine the prevalence of intimate partner violence (IPV), and associated factors, in reproductive-aged women attending psychiatric outpatient departments.Design Cross-sectional facility-based study.Setting Outpatient psychiatric clinics of public hospitals in Addis Ababa.Participants Reproductive aged women with chronic mental illness (CMI) who attended follow-up in psychiatric outpatient clinics.Primary and secondary outcome measures The data were collected using a multi-culturally validated instrument from randomly sampled women with CMI. Multiple logistic regression was used to identify factors independently associated with IPV.Result Four hundred and twenty-two women who were attending the psychiatric outpatient clinics took part in the study. The majority of participants 62.0% (95% CI 56.1 to 68.8) experienced IPV at least once in their lifetime. The most common form of IPV experienced by women was emotional violence (60%; 95% CI 55.0 to 64.7). One hundred and eighty-six (44.1%; (95% CI 39.3 to 48.8)) respondents experienced physical or sexual violence during the last year. A history of divorce (Adjusted Odds Ratio [AOR]=5.64; 95% CI 2.75 to 11.56) and having a mental illness for more than 5 years (AOR=2.23; 95% CI 1.26 to 3.93) were associated with any form of IPV.Conclusion The high prevalence of IPV among women attending psychiatric outpatient services highlights the need to routinely inquire about IPV and develop effective strategies to prevent it among this vulnerable group.